Characteristics of PPROM in General Hospital Dr. Soetomo Surabaya Period September 2017 to September 2019 - Alessandrini, Letizia; Wicaksono, Budi (Jurnal Medis Islam Internasional, 2021)
Background: Preterm Prelabour Rupture of Membranes (PPROM) is one of the causes of perinatal morbidity and mortality. Objective: To find out the characteristic of PPROM in Dr. Soetomo Hospital in September 2018 to September 2019. Method: A Retrospective Descriptive Study. The data came from the medical records of patients with PPROM who were included in the inclusion criteria. The exclusion criteria is all PPROM cases at Gestational age > 34 weeks. Result: The incidence of PPROM during September 2017 to September 2019 was 6.8% (175 patients), of which 152 patients included NBC cases and 23 patients with BC cases. Primipara 76 patients and Multipara 99 patients. For gestational age <26 weeks it was 17.1%, 26-30 weeks 29.7% and 31-34 weeks 53.1%. In this study, PPROM was amused 23.6%, underweight 3.1%, HBsAg 7.5%, HIV 7%, anemia 10.3%, Obesity 5.2%, Pragestational Diabetes 7.4%, Gestational Diabetes. 2,6%, preeclampsia 7,9% and severe preeclampsia 2,2%. The distribution of PPROM patients who received lung maturation was 72%, while the remaining 28% did not get lung maturation. Type of delivery for PPROM cases was vaginal delivery as much as 60% while 40% for cesarean section. Indications for vaginal delivery include fetal distress 25%, abnormal NST 18%, gemeli 17%, BSC 12%, febris 10%, pulmonary edema 5% and breech presentation 5%. The outcome distribution of PPROM infants born with asphyxia at birth was 87%. Weight of babies born with PPROM> 2500 g 4%, 1000-2500 g 73% and <1000 g 23%. The condition of the babies at birth with spontaneous breathing was 36 babies, nasal O2 was 13 babies and CPAP was 70 babies. The causes of death for preterm KPP babies included RDS 9 babies, Sepsis 4 babies and severe asphyxia 19 babies. The length of NICU care for infants who died with KPP Preterm mothers was <24 hours for 15 babies, 1-3 days 13 babies, 4-7 days 3 babies,> 7 days 3 babies and 5 fetuses were IUFD. 12 patients with PPROM received amnioinfusion while 5 patients with amniopatch, Outcome of infants from conservative PPROM who were treated with amniopatch or amnioinfusion obtained 6 babies died at birth, 8 babies with CPAP breath support, 1 baby with PCV breath support, 1 baby with ventilator and 1 infant spontaneously breathed. A total of 3 babies were outpatient after treatment for a maximum of ± 25 days. Conclusion: Perinatal care is currently experiencing some rapid progress, but the case of PPROM is still one of the biggest contributors to perinatal morbidity and mortality.